Cyanobacteria Growth Kinetics - Giannuzzi, Leda (2019)
Cyanobacterial blooms are a global problem for freshwater ecosystemsused for drinking water supply and recreational purposes. Cyanobacteria alsoproduce a wide variety of toxic secondary metabolites, called cyanotoxins. Highwater temperatures have been known to lead to cyanobacterial bloom developmentin temperate and semiarid regions. Increased temperatures as a result of climatechange could therefore favor the growth of cyanobacteria, thus augmenting therisks associated with the blooms. Though temperature is the main factor affecting the growth kinetics of bacteria, the availability of nutrients such as nitrogen and phosphorus also plays a significant role. This chapter studies the growth kinetics of toxin-producing Microcystis aeruginosa and evaluates potential risks to the population in scenarios of climate change and the presence of nutrients. The most suitable control methods for mitigation are also evaluated.